Aplikasi Probiotik Probio_FM untuk Meningkatkan Pertumbuhan Ikan Patin (Pangasianodon Hypophthalmus) di Desa Sungai Duren, Kabupaten Muaro Jambi - Fahmida; Damhuri, Dedi; Nurhayani; Rolin, Febrina; Sri Wahyuni, Eka (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
This community service activity aims to improve feed quality and performance of catfish cultivation in “Karya Mandiri” business partners through the application of Probio_FM probiotic fish pellets. The activity was carried out in four stages: (1)preparation, including discussions with partners to identify feed production conditions, raw materials, mixing techniques, drying methods, as well as socialization of probiotic concepts; (2) making probiotic pellets, including mixing local raw materials, UV-based drying and adding Probio_FM at a dose of 10 mL/kg of feed; (3) feeding and maintaining fish at a density of 40 fish/m² for 30 days, feeding twice a day ad satiation, and sampling growth every 10 days; and (4) monitoring and evaluation of fish growth. The results showed that fish fed Probio_FM experienced higher growth in length and weight compared to treatments without probiotics. On the 30th day, the average length of fish with probiotics reached 12.95 cm and a weight of 23.03 g, compared to only 12.43 cm and 20.35 g for fish without probiotics. This indicates that probiotics improve feed efficiency, nutrient absorption, and overall fish health. Probio_FM supports growth by improving gut microflora, increasing digestive enzyme activity, controlling pathogenic bacteria, and increasing disease resistance. Furthermore, the use of probiotics contributes to sustainable cultivation by reducing organic waste and improving pond environmental quality. The results of this community service program confirm that Probio_FM probiotic feed into catfish cultivation has the potential to increase productivity, feed efficiency, and environmentally friendly cultivation practices, while also providing economic benefits to business partners